ANALYSIS OF QUALITY OF SERVICE IN SOFTWARE DEFINED NETWORKS USING THE OPENDAYLIGHT CONTROLLER WITH PREPARE, PLAN, DESIGN, IMPLEMENT, OPERATE, OPTIMIZE METHOD - Saputra, Dewaldi; Kurniawan, Mochamad Teguh; Fathinuddin, Muhammad (STKIP PGRI Tulungagung, 2025)
The research presented in this paper analyzes QoS in SDN with an OpenDaylight controller through the Prepare, Plan, Design, Implement, Operate, Optimize (PPDIOO) method, which analysis limited to the Design stage. The emulator in the simulation is utilizing Mininet, and the tree topologies are examined and tested for their relative QoS under normal and abnormal traffic, or during DDoS attacks, using Hping3. Under normal condtions with three hosts, the bandwidth remains at 99.8 Mbits/s, jitter 0.018ms, packet loss 0.143%, and throughput 95Mbit/s. Using seven hosts, the average bandwidth was 74.9 Mbit/s, with a jitter of 0.448 ms and a packet loss of 0.257%, for a throughput of 71.5 Mbit/s. With 13 hosts, the bandwidth drops to 41.7 Mbit/s, with jitter of 5,768 ms per packet. With one attacker, the band-width reduced to 526 Mbit/s, jitter to 0.021 ms, packet loss to 0.3%, and throughput to 490.7 Mbit/s. There was 63.9 Mbit/s bandwidth, 2563 ms jitter, 20% packet loss, and 59.4 Mbit/s throughput with three attackers. Seven attackers reduced the bandwidth to 11 Mbit/s, with jitter of 3814 ms, packet loss of 60%, and a throughput of 10.5 Mbit/s. In the event of 12 attackers, bandwidth dropped to 3.24 Mbit/s, jitter to 21,544 ms, packet loss to 80%, and throughput to 3.1 Mbps. Generally, QoS on SDN with OpenDaylight controller is significantly degraded during DDoS attacks; thus, an excellent management plan is required to maintain optimal QoS.